Zarządzanie środowiskiem w aspekcie zrównoważonego rozwoju gospodarczego: Environmental management in the scope of economic sustainable development - Marciniuk-Kluska, Anna (Management and Administration Journal, 2021)
Sustainable development is the right to fulfil the developmental aspirations of the contemporary population without limiting the rights of future generations. This means that the economic and civil development of the present generation should not restrict any rights of future generations or be obtained at their cost. Sustained development should respect the rights of nature and the economy by obeying the rule of purpose, rules in a given region, and the rule of quality, and taking into account the economies of the scale. The main purpose of this paper is to present management instruments for sustainable development and ecological education as an important issue in promoting sustainable development and environmental management.